DROUGHT TOLERANCE IN RICE AND ROLE OF WRKY GENES - S. Kanwal; S. Jamil; N. Afza; I. Ghafoor; M. Shehzadi; R. Kanwal; M. Z. Iqbal (Journal of Animal and Plant Sciences, 2022)
Anthropogenic alteration in climate has resulted in devastating global issue of drought for rice crop. Drought interferes with all the growth stages of crop by delaying its growth mechanisms, metabolic pathways and reducing the spikelet fertility. Rice plant has developed some morphological and physiological mechanisms to cope with the stress which include reduction in photosynthesis and transpiration, increased stomatal conductivity and density, root to shoot ratio, root length and carbon assimilation. Some biochemical modifications like biosynthesis of various hormones (ABA) and proteins (proline) also help in reducing the yield losses. Marker assisted selection and Quantitative Trait Loci (QTL) mapping are the advanced molecular techniques that played a vital role in developing the improved and stress tolerant rice cultivars. Identification of different stress responsive genes and transcriptional factors especially WRKY TFs have provided platform to obtain good crop stand and yield even under stress conditions. Rice possesses more WRKY genes (109 WRKY TFs in rice) as compared to Arabidopsis thaliana. An enormous variation in the expression patterns of WRKY genes and their contribution to the amplification of various signaling pathways and regulatory networks has been observed. These transcription factors work by regulating different mechanisms of drought tolerance and by releasing hormones, proteins, reducing-sugars, solutes and by affecting the stomatal conductance and root architecture. The WRKY genes work by showing up- and down- regulation to proteins, various protein-protein interactions and cross-regulation of WRKY TFs. Advance breeding methods; MAS, GWS, MABC, MARC and biotechnological tools along with different WRKY transcription factors have dynamically contributed in developing abiotic and biotic stress resistant rice varieties/cultivars on large scale.
Keywords: Drought stress; WRKY TFs; QTLs; Biotechnological approaches; Rice breeding